HDAC6 and Ovarian Cancer - Haakenson, Joshua (Molecular Diversity Preservation International (MDPI), 2013)
The special class IIb histone deacetylase, HDAC6, plays a prominent role in many cellular processes related to cancer, including oncogenesis, the cell stress response, motility, and myriad signaling pathways. Many of the lessons learned from other cancers can be applied to ovarian cancer as well. HDAC6 interacts with diverse proteins such as HSP90, cortactin, tubulin, dynein, p300, Bax, and GRK2 in both the nucleus and cytoplasm to carry out these cancerous functions. Not all pro-cancer interactions of HDAC6 involve deacetylation. The idea of using HDAC6 as a target for cancer treatment continues to expand in recent years, and more potent and specific HDAC6 inhibitors are required to effectively down-regulate the tumor-prone cell signaling pathways responsible for ovarian cancer.